Research RESEARCH ON THE CHALLENGES AND WAYS TO IMPROVE THE COMPREHENSIVE ABILITY OF CHINESE MUSIC EDUCATORS IN THE FUTURE (Proceedings of the International Conference on Future of Education, 2022)
Music education, as an important form of music broadcasting, provides students with excellent aesthetic experience, cultivates their sentiment, develops their creative thinking, and also inherits the excellent cultural tradition, enriches the connotation of the world music culture, and promotes interpersonal communication and emotional communication. Music educators, as the main media of music communication, have a great responsibility. With China’s rapid economic development, people’s continuous pursuit of artistic quality, music educators is facing greater challenges. Facing this in the future, they urgent need to improve their comprehensive ability. This paper studied through literature and comparative study. Through the literature method, it consults the relevant literature at home and abroad, defines and explains the relevant core concepts, defines the content of the comprehensive ability of future music educators, and summarizes the current situation of music education in China. Through the comparative research method, the development course of Chinese music education is compared, and the experience and lessons are summarized. Finally, combined with the current actual situation of music education in primary and secondary schools in China, effective suggestions and opinions were put forward on the improvement of the comprehensive ability of music education educators in the future. This paper is divided into 3 parts. The first part reviews the contents of the comprehensive abilities of music educators. The second part analyzes the development process of Chinese music education and the current challenges. The third part puts forward the future music educators to improve the comprehensive ability.
Keywords: Future music educators; comprehensive ability; challenges; improvement